Effects of ambient illumination, contrast polarity, and letter size on text legibility under glance-like reading. - Dobres, Jonathan; Chahine, Nadine; Reimer, Bryan (Applied Ergonomics, 2017)
Recent research on the legibility of digital displays has demonstrated a "positive polarity advantage", in which black-on-white text configurations are more legible than their negative polarity, white-on-black counterparts. Existing research in this area suggests that the positive polarity advantage stems from the brighter illumination emitted by positive polarity displays, as opposed to the darker backgrounds of negative polarity displays. In the present study, legibility thresholds were measured under glance-like reading conditions using a lexical decision paradigm, testing two type sizes, display polarities, and ambient illuminations (near-dark and daylight-like). Results indicate that legibility thresholds, quantified as the amount of time needed to read a word accurately, were highest for the negative polarity configurations under dark ambient illumination, indicated worse performance. Conversely, the positive polarity conditions under dark ambient illumination and all conditions under bright illumination demonstrated significantly reduced thresholds, indicating greater legibility. These results are consistent with the hypothesis that the "positive polarity advantage" arises because brighter illumination produces pupillary contraction that reduces optical aberrations as light enters the eye. These results have implications for the design of automotive interfaces and other scenarios in which an interface must be optimized for glance-like reading under variations in ambient lighting conditions.